2020
DOI: 10.2306/scienceasia1513-1874.2020.062
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm activity of Thai herbal essential oils against Staphylococcus pseudintermedius causing canine pyoderma

Abstract: The aim of this study was to investigate the efficacy of 11 essential oils (EOs) against Staphylococcus pseudintermedius planktonic and biofilm forms. Twenty three bacterial samples were collected from dogs with superficial pyoderma and 9 samples were identified as S. pseudintermedius by polymerase chain reaction-restriction fragment length polymorphism method. The minimum planktonic inhibitory concentration (MPIC), minimum planktonic bactericidal concentration (MPBC) and minimum biofilm eradication concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…This study demonstrated that all three essential oils had a good eradicating effect on the common bovine mastitis pathogens, S. aureus, S. agalactiae, and E. coli. The time-kill assays indicated that the antibacterial effects of these essential oils were dependent on both dose and time, which [8,22], in accordance with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that all three essential oils had a good eradicating effect on the common bovine mastitis pathogens, S. aureus, S. agalactiae, and E. coli. The time-kill assays indicated that the antibacterial effects of these essential oils were dependent on both dose and time, which [8,22], in accordance with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The control bacterium S. pseudintermedius ATCC 49051 was obtained from the American Type Culture Collection (ATCC), Virginia, USA. All strains were cultured in Mueller Hinton broth (MHB) (Becton Dickinson, France) and incubated at 37 °C for 24 h. Inocula were prepared by adjusting overnight cultures to 10 6 -10 7 CFU/ml by measuring the optical density (OD) at 600 nm [10].…”
Section: Microbial Strains and Culture Conditionsmentioning
confidence: 99%
“…The bacteria were Gram-positive cocci arranged in grapelike clusters and produced pinpoint colonies that showed beta haemolysis on blood agar. Bacteria that were catalase and coagulase positive, oxidase and hyaluronidase negative, and produced acid from mannitol, sucrose, and trehalose were confirmed to be S. pseudintermedius by PCR-restriction fragment length polymorphism (PCR-RFLP) method as described previously [12]. Briefly, DNA was extracted by BacterialXpress™ nucleic acid extraction kit (Chemicon, Germany) and replicated using primers: pta_f1 (5 -AAA GAC AAA CTT TCA GGT AA-3 ) and pta_r1 (5 -GCA TAA ACA AGC ATT GTA CCG-3 ) (Bio Basic Canada Inc., Canada).…”
Section: Bacterial Collection and Identificationmentioning
confidence: 99%